Validation of the Cognitive Assessment Instrument for Obsessions and Compulsions (CAIOC-13) in an Indian Sample - Mahashweta Bhattacharya; Himani Kashyap; Srinivas Balachander; Y. C. Janardhan Reddy (Indian Journal of Psychological Medicine)
Background: Brief self-report measures of cognition are advantageous for flagging significant cognitive dysfunction without extensive neuropsychological assessments. The Cognitive Assessment Instrument for Obsessions and Compulsions (CAIOC-13) is a recently developed self-report that assesses everyday cognitive dysfunction in obsessive-compulsive disorder (OCD), for example, difficulties with reading, slowness, and decision-making. This study was undertaken to validate the CAIOC-13 in an Indian sample of OCD. Methods: 75 subjects with OCD and 81 non-clinical controls completed CAIOC-13, Perceived Deficits Questionnaire (PDQ), and Dysfunctional Attitude Scale-Short Form (DAS-SF1). Convergent and divergent validity with PDQ and DAS-SF1 were established with Pearson’s correlation; the Receiver Operating Characteristic (ROC) curve was used to analyze discriminant validity; and factorial structure was evaluated using the principal component analysis (PCA). Results: CAIOC-13 scores showed a strong significant correlation ( r = 0.56; p < .001) with PDQ and a moderate correlation with DAS-SF1 scores ( r = 0.33; p = .003). CAIOC-13 could accurately discriminate between OCD and controls (area under curve = 0.92). PCA revealed strong loading on a single component. Conclusion: CAIOC-13 is a valid tool for briefly assessing OCD-related cognitive dysfunction in Indian samples. Future studies may examine the correlation of CAIOC-13 with standardized neuropsychological assessments.